2015
DOI: 10.1158/1538-7445.am2015-4280
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 4280: Utilizing a selective agonist of the intermediate-affinity IL-2 receptor with an improved pharmacokinetic profile leads to an enhanced immunostimulatory response With reduced toxicity in mice

Abstract: RDB 1450 is an engineered fusion protein which selectively activates the intermediate-affinity IL-2 receptor present on NK cells and memory CD8 T cells. In rodents, RDB 1450 has a half-life of 6-8 hours, compared to a half-life of minutes for recombinant human IL-2 (rhIL-2). Repeat daily dosing (QD) of RDB 1450 in mice results in marked expansion of NK cells and CD8+CD44high T cells, with minimal expansion of CD4+ regulatory T cells (Tregs). Higher QD doses elicit more pronounced effector cell expansion with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In tumor models, it showed higher efficacy and tolerability than wild-type IL-2 49 . Recently, RDB 1450 was described, an engineered fusion protein of permuted IL-2 and CD25 that is selective for IL-2Rβγ and was found to have improved PK properties and to mediate a marked expansion of NK and CD8 + T cells, but not Tregs, and exhibited reduced toxicity in mice 50 . Most recently, Sim and colleagues showed that IL2 F42K circumvented Treg expansion and promoted NK activation, 51 and Ghasemi and colleagues described a fusion protein of an IL-2 R38A/F42K double mutant with reduced CD25 binding fused to cowpox virus encoded NKG2D binding protein (OMCP) to target IL-2 to NKG2D positive immune cells such as NK cells 52 …”
Section: Discussionmentioning
confidence: 99%
“…In tumor models, it showed higher efficacy and tolerability than wild-type IL-2 49 . Recently, RDB 1450 was described, an engineered fusion protein of permuted IL-2 and CD25 that is selective for IL-2Rβγ and was found to have improved PK properties and to mediate a marked expansion of NK and CD8 + T cells, but not Tregs, and exhibited reduced toxicity in mice 50 . Most recently, Sim and colleagues showed that IL2 F42K circumvented Treg expansion and promoted NK activation, 51 and Ghasemi and colleagues described a fusion protein of an IL-2 R38A/F42K double mutant with reduced CD25 binding fused to cowpox virus encoded NKG2D binding protein (OMCP) to target IL-2 to NKG2D positive immune cells such as NK cells 52 …”
Section: Discussionmentioning
confidence: 99%